A comment on "A fast L_p spike alignment metric" by A. J. Dubbs, B. A. Seiler and M. O. Magnasco [arXiv:0907.3137] - HOUGHTON, CONOR JAMES (My University, 2009)
Measuring the transmitted information in metric-based clustering has become something of a standard test for the performance of a spike train metric. In this comment, the recently proposed L_p Victor-Purpura metric is used to cluster spiking responses to zebra finch songs, recorded from field L of anesthetized zebra finch. It is found that for these data the L_p metrics with p>1 modestly outperform the standard, p=1, Victor-Purpura metric. It is argued that this is because for larger values of p, the metric comes closer to performing windowed coincidence detection.
PUBLISHED
Keywords: Pure & Applied Mathematics